The impact of court-connected alternative dispute resolution on the dispensation of civil justice in Nigeria : a comparison with South Africa and the United States of America - Olagbegi-Oloba, Victoria Banke (Stellenbosch : Stellenbosch University, 2025)
Thesis (LLD)--Stellenbosch University, 2024.